Pentingnya Membentuk Budaya Antikorupsi Dilihat dari Perspektif Pertanggungjawaban Pidana Korporasi - Nani Mulyati (Faculty of Law, Andalas University, 2019)
One of the potential actors in corruption is a corporation. An important curative effort to eradicate corruption is to ensure that all perpetrators of corruption are accountable for their actions, including corporations as legal subjects; but preventive efforts are also important. One effort to prevent the occurrence of criminal acts of corruption that can be committed by corporations is to form a law-abiding and anti-corruption corporate culture. This paper tries to analyze the role of corporate culture on corrupt behavior that exists in corporations and the legal implications in criminal cases when corporations have implemented a culture of anti-corruption. This study employs doctrinal method, by analyzing legal materials. From the research conducted, it is recommended to arrange clearer regulation pertaining justifications for corporate criminal liability, and for corporations it is recommended that they form an effective and consistent anti-corruption culture in order to ensure that corporate policy is clearly against all forms of corruption carried out by corporate organs or executives. With the implementation of an anti-corruption culture within the corporation, it is expected that every member of the corporation will be very careful in preventing corruption, which can be considered as an act that represents the corporation. If the corporation has implemented an anti-corruption corporate culture, then in theory it should be accepted as one of the reasons to alleviate criminal liability for corporations as a form of justification “afwezigheid van alle schuld” (avas).